116k views
4 votes
How is the graph of log (x – 2) + 1 translated from the graph of log x?

1 Answer

4 votes

Answer:

See the two translations described below

Explanation:

Start with the graph of y = log x. This graph passes through (1, 0) and exists only for x > 0. The line x = 0 is its vertical asymptote.

Translating this graph 2 units to the right results in h(x) = log (x - 2).

Translating the graph of h(x) = log (x - 2) upward by 1 unit results in the graph of log (x – 2) + 1.

User MunHunger
by
5.0k points